Investigation of shielding properties of impregnated activated carbon for gamma-rays - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Carbon related structures are extraordinarily attractive materials for researchers and especially for organic chemistry, besides being the most important basic materials of daily life. The richness of various optical and electronic behaviors has made them one of the rapidly rising materials on the horizon of material science and condensed matter physics. Having the sheets of atoms that are stacked in a disorganized manner makes activated carbon being different from other forms of carbon -graphite- structures. The researches about the shielding properties of activated carbon atoms for gamma-rays are very rare and required to be improved. Since the use of radioactive sources in different fields (nuclear industry, shielding material, radiation biophysics and space research application, etc.) has been increasing expeditiously, the photon interactions with matter has gained more importance in the world of material science technology. In this article, we review the basics of the impregnated activated carbons (AC1 and AC2), as well as the link between the structural behaviors and the gamma shielding properties in terms of both quality and efficiency. Both XCom software and EGSnrc simulation code were used to obtain the theoretical calculations that are significantly important to be able to understand the shielding properties of impregnated activated carbons (AC1 and AC2) for gamma-rays. At the end, the mass attenuation coefficients (mu(m)), the total atomic and the electronic cross-sections (sigma(t,a) and sigma(t,e)), the effective atomic number and the effective electron density (Z(eff) and N-eff), the half value layer (HVL), the tenth value layer (TVL), and the mean free path (MFP) values of such materials were calculated and then compared with those of some other known shielding materials like lead, borosilicate, concrete and vermiculite. The calculated data showed that impregnated activated carbons (AC1 and AC2) are very appropriate and consistent to be one of the candidates for shielding materials of gamma-rays.
Keywords: Impregnated activated carbon; Absorption; Shielding material; Gamma-rays; ATTENUATION; GLASSES; PARAMETERS; ADSORPTION; CONCRETE